Social distancing in light of the covid-19 pandemic and the problematic of domestic violence in Algerian society - Lamraoui, Zakia; Tamrabet, Noura (Journal of Human Sciences, 2020)
The present study aimed to uncover the aggressive practices within the family pattern in the Algerian society in light of social distancing measures. The descriptive approach was used to investigate the dimensions of the problem represented in identifying the causes of domestic violence and revealing the nature of aggressive practices, as well as an objective explanation of the nature of domestic violence practiced against women. A questionnaire was distributed to an accidental sample that included 240 individuals. The results showed that the confinement produced a set of negative indicators within the family, such as lack of understanding, poor communication, fragility of family links, which resulted in a group of aggressive behaviors that take a moral aspect such as psychological neglect, insulting and bullying, in addition to the aggressive act practiced against women by members of her family morally and physically.